Haval-Argade contrathermodynamic rearrangement of alkylidenesuccinimides to alkylmaleimides via the corresponding isoimides: a general approach to alkyl and dialkyl substituted maleimides - Haval, Kishan P.; N. P. Argade (Tetrahedron, 2006)
A simple and efficient access to alkyl and dialkyl substituted maleimides has been demonstrated via the new contrathermodynamic rearrangement of (E)-alkylidenesuccinimides to alkylinaleimides. The (E)-alkylidenesuccinimides obtained from the Wittig-condensation of N-arylmaleimide with aliphatic aldehydes oil regioselective hydrolysis furnished the corresponding (E)-alkylidenesuccinanilic acids in 95-98% yields. The beta-alkylidenesuccinanilic acids oil treatment with cyanuric chloride in the presence of triethylamine gave the corresponding beta-alkylisomaleimides in 78-80% yields via the beta-alkylideneisosuccinimides with the exocyclic to endocyclic carbon-carbon double bond migration. The kinetically controlled products alkylisomaleimides in refluxing acetic acid furnished the thermodynamically controlled alkylinaleimides in 98% yield. The Wittig condensation of alkyl substituted isomaleimides/maleimides with aliphatic aldehydes gave the desired dialkyl substituted maleimides in high yields. A conversion of alpha-methylenesuccinanilic acids to alpha-methylisomaleimides has also been described, with 90% yield. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alkyl and dialkylmaleimides; contrathermodynamic rearrangement; isomaleimides; maleimides; wittig coupling